A positive psychology perspective on quality of life (Springer Netherlands :, 2013)
Most people strive for happiness, or subjective well-being (SWB), and a high quality of life (QoL) in all areas of their lives. To do so, many have to overcome adversity on a frequent basis. The field of positive psychology, which focuses on human strengths and positive emotions, not only offers people tools to help achieve optimal levels of subjective well-being and quality of life regardless of their circumstances, it also enables us to understand how people utilize such qualities as hope, optimism, resilience, interest, wisdom, altruism, religiosity and spirituality to best cope with adversity. By exploring the latest research in subjective well-being and quality of life, this book shows how qualities of positive psychology interact in a wide variety of contexts in the everyday lives of people. It details evidence from children to the elderly, from marital to professional to school life, from healthy people to those suffering some sort of malediction. And the studies are presented by researchers from various parts of the globe, thereby offering an international and cross-cultural perspective to subjective well-being, quality of life and positive psychology. 1. Introduction - Anastasia Efklides and Despina Moraitou -- Part I: Quality of life, well-being, and positive psychology -- 2. Hierarchical needs, income comparisons and happiness levels - Stavros A. Drakopoulos -- 3. Goals and plans: Their relationship to well-being - Andrew MacLeod -- 4. Living in accordance with one's implicit motives: Cross-cultural evidence for beneficial effects of motive-goal congruence and motive satisfaction - Jan Hofer and Holger Busch -- 5. Positive psychology and subjective well-being homeostasis: A critical examination of congruence - Robert A. Cummins -- 6. Life satisfaction in adults: The effect of religiosity, worry and perceived physical health state - Maria Platsidou -- 7. Altruism and health: Theoretical perspectives - Carolyn E. Schwartz, Brian R. Quaranto, and Kurt Gray -- 8. Marital quality and well-being: The role of gender, marital duration, social support and cultural context - Eleni Pateraki and Pagona Roussi -- Part II: Positive psychology and human strengths -- 9. The role of dispositional optimism in physical and mental well-being - Nathaly Rius-Ottenheim, Roos C. van der Mast, Frans G. Zitman, and Erik J. Giltay -- 10. The relation of optimism to cardiac patients’ subjective health through illness representations: Does the level of optimism matter? - Evangelos C. Karademas, Elvisa-Foteini Frokkai, Evangelia Tsotra,  and Rania Papazachariou -- 11. Wise thinking, hopeful thinking, and positive aging: Reciprocal relations of wisdom, hope, memory, and affect in young, middle-aged, and older adults - Despina Moraitou and Anastasia Efklides -- 12. Dispositional hope and action-state orientation: Their role in self-regulated learning - Georgia Papantoniou, Despina Moraitou, Magda Dinou, and Effie Katsadima -- 13. One ingredient in the mix: Interest and psychological well-being - Mary Ainley -- 14. From burnout to engagement during transition from school to work - Katariina Salmela-Aro -- 15. A comparative study lience in Greece and Cyprus: The effects of negative life events, self-efficacy and social support on mental health -- Sophie Leontopoulou -- 16. Subject Index.